Improved effect of ultrasound-assisted enzymolysis on egg yolk powder: Structural properties, hydration properties and stability characteristics. (15th July 2022) - Li, Qiqi; Zhang, Xinyue; Tang, Shitao; Mi, Sijie; Lu, Lizhi; Zeng, Qi; Xia, Minquan; Cai, Zhaoxia
Highlights: Egg yolk powder with high solubility and excellent dispersion stability was prepared. The yolk proteins sonicated at 60 W for 20 min had the highest degree of hydrolysis. Ultrasound-assisted enzymolysis led to smaller particle size of yolk particles. Ultrasound treatment enhanced the hydrogen bonding forces between proteins. Abstract: Preparation of egg yolk powder (EYP) with excellent hydration properties and dissolution stability is important for the efficient utilization of its functional properties and nutritional properties in food. In this work, a new method utilizing ultrasound-assisted enzymolysis (UP-EM) was investigated to obtain EYP. Compared to enzymolysis-alone treated (EM), ultrasonic pre-treatment (UP) significantly increased the enzymatic hydrolysis rate by 106.28%. In particular, the UP 60 W 20 min-EM group obtained the desired solubility and coefficient of stability. The observed microstructure of EYP showed that the egg yolk particles obtained by UP-EM were more uniformly distributed and smaller in particle size. The protein structure was confirmed by Fourier transform infrared spectrum, which showed that UP enhanced the hydrogen bonding force between egg yolk proteins. Therefore, it can be believed that UP-EM can significantly improve the hydration properties and dispersion stability of EYP, laying the foundation for its wide applications in food industry.